EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION - Iskandar Ahmaddien (JURNAL ILMIAH EDUNOMIKA, 2024)
In order to increase job satisfaction and employee performance, something called work-life balance is needed. Work-Life Balance is an individual's ability to balance work and personal life. This research aims to determine the effect of work-life balance on employee performance with job satisfaction as a mediating variable. The population and sample in this study were private employees spread across Indonesia who were obtained using a probability sampling technique: simple random which was successfully obtained as many as 150 respondents, the analysis technique used Smart PLS. The research results show that work-life balance influences employee performance and job satisfaction, job satisfaction influences employee performance, and job satisfaction is able to mediate work-life balance on employee performance. Keywords: Work-Life Balance, Employee Performance, Job Satisfaction